Seasonal variation of Nitrate-N in groundwater: A case study from Chunnakam aquifer, Jaffna Peninsula - Sutharsiny, A.; Manthrithilaka, H.; Pathmarajah, S.; Thushyanthy, M.; Vethanage., M. (University of Peradeniya, 2014)
The Jaffna Peninsula has four main aquifer systems. The largest of these is the Chunnakam aquifer in the Valikamam area. Intensive cultivation in this area has led to groundwater pollution, which is due to the excessive use of inorganic and organic ni- trogen fertilisers. The situation is aggravated by excessive irrigation applications, which carries the fertiliser applied to the groundwater almost on a daily basis. In addi- tion, the heavy rainfall experienced during the wet season not only carries the nitrogen to groundwater but also brings the groundwater level close to the surface. As a result, the fertiliser residues remain in the upper layers and also get dissolved in the ground- water. The aim of this study was to assess the spatial and temporal variation of ni- trate-N contamination in drinking water in the Chunnakam aquifer, which was a sub- objective of a research project carried out by the International Water Management In- stitute (IWMI). Forty-four wells representing different uses and land-use patterns were monitored on a monthly basis over a period of one year from January to Decem- ber, 2011. Nitrate-N concentrations in the water samples were determined using a colorimetric spectrophotometer. The spatial variations of water quality were mapped using ArcGIS 10.1.